Is virtual reality effective to teach prevention of surgical site infections in the operating room?: study protocol for a randomised controlled multicentre trial entitled VIP room study - Masson, Claire; Birgand, Gabriel; Castro-Sánchez, Enrique; Eichel, Vanessa; Comte, Alexa; Terrisse, Hugo; Rubens-Duval, Brice; Gillois, Pierre; Albaladejo, Pierre; Picard, Julien; Bosson, Jean Luc; Mutters, Nico T.; et al. (BMJ open, 2020)
Introduction Some surgical site infections (SSI) could be prevented by following adequate infection prevention and control (IPC) measures. Poor compliance with IPC measures often occurs due to knowledge gaps and insufficient education of healthcare professionals. The education and training of SSI preventive measures does not usually take place in the operating room (OR), due to safety, and organisational and logistic issues. The proposed study aims to compare virtual reality (VR) as a tool for medical students to learn the SSI prevention measures and adequate behaviours (eg, limit movements…) in the OR, to conventional teaching. - Methods and analysis This protocol describes a randomised controlled multicentre trial comparing an educational intervention based on VR simulation to routine education. This multicentre study will be performed in three universities: Grenoble Alpes University (France), Imperial College London (UK) and University of Heidelberg (Germany). Third-year medical students of each university will be randomised in two groups. The students randomised in the intervention group will follow VR teaching. The students randomised in the control group will follow a conventional education programme. Primary outcome will be the difference between scores obtained at the IPC exam at the end of the year between the two groups. The written exam will be the same in the three countries. Secondary outcomes will be satisfaction and students’ progression for the VR group. The data will be analysed with intention-to-treat and per protocol. - Ethics and dissemination This study has been approved by the Medical Education Ethics Committee of the London Imperial College (MEEC1920-172), by the Ethical Committee for the Research of Grenoble Alpes University (CER Grenoble Alpes-Avis-2019-099-24-2) and by the Ethics Committee of the Medical Faculty of Heidelberg University (S-765/2019). Results will be published in peer-reviewed medical journals, communicated to participants, general public and all relevant stakeholders.
Gesehen am 25.09.2020